Silane crosslinking of poly(lactic acid): The effect of simultaneous hydrolytic degradation - M. Rahmat; I. Ghasemi; M. Karrabi; H. Azizi; M. Zandi; M. Riahinezhad (eXPRESS Polymer Letters, 2015)
In this work, silane crosslinking of poly (lactic acid) (PLA) was studied. PLA was grafted with vinyl-trimethoxysilane (VTMO) via melt mixing in an internal mixer, followed by a crosslinking reaction in hot water for different times. The effect of simultaneous hydrolytic degradation in hot water (70°C) during crosslinking was monitored. Silane grafting of PLA was characterized using mixing torque and gel permeation chromatography (GPC) analysis. The results revealed that by increasing the silane (0–7 wt%) and peroxide (0–0.5 wt%) contents, the degree of grafting was increased. A peak corresponding to higher molecular weight in GPC chromatograms appeared in comparison to pure PLA due to the grafting reaction. Gel content, swelling test, GPC and thermal gravimetric analysis (TGA) were performed to monitor gel structure and concurrent hydrolytic degradation. Results confirmed that the occurrence of hydrolytic degradation during crosslinking and gel content of some samples tended to zero over 10 hr of immersion in hot water. The effect of hydrolytic degradation was not significant up to 10 hr and a tight gel structure was obtained. However, at longer crosslinking times, hydrolytic degradation was the dominant mechanism that leads to network defects.